Sex-specific associations of the endocrine-disrupting chemicals with serum neurofilament light chain among US adults - Kaiting Hong; Haoyue Cheng; Yan Zhuang; Yunxian Yu (Ecotoxicology and Environmental Safety)
Objective: Endocrine-disrupting chemicals (EDCs) can interfere with endocrine function and lead to neurological damage. Neurofilament light chain (NfL) is a protein released into the blood after neuroaxonal damage, and it has become a dependable biomarker for neurological conditions. The study aimed to investigate the associations between single or combined EDCs exposure and serum NfL levels in adults. Methods: The 1372 participants included in the study were from the 2013–2014 National Health and Nutrition Examination Survey. Due to the difference in types of EDCs, participants were divided into two populations. Multiple linear regression models were used to assess the association between 32 EDCs and NfL. The least absolute shrinkage and selection operator regression model was used for EDCs selection and the weighted quantile sum (WQS) regression was used for examining the association of EDCs mixture with NfL and identify the predominant exposure. Results: Levels of urinary bisphenol S, mono(2-ethylhexyl) phthalate, dibutyl phosphate, glyphosate, and 3,5,6-trichloropyridinol were positively associated with serum NfL levels, while benzophenone-3, methylparaben, and propylparaben showed negative associations. In the WQS regression model, the changes of NfL were 0.154 (95 % CI: 0.014–0.294) and 0.164 (95 % CI: 0.033–0.296) for each quartile increase in WQS index of EDCs mixture in the two populations, respectively. Analysis of the subgroup with gender stratification suggested that the association between EDCs mixture and NfL was only significant in men. The positive mixture β was 0.219 (95 % CI: 0.056–0.380) and 0.257 (95 % CI: 0.082–0.433) in the two population, respectively. Conclusion: The study suggested a potential association between single or combined exposure to EDCs and NfL levels. High-level EDCs exposure might be associated with more severe neurological damage, particularly in men.